2010
DOI: 10.1371/journal.pone.0009626
|View full text |Cite
|
Sign up to set email alerts
|

Task Shifting Routine Inpatient Pediatric HIV Testing Improves Program Outcomes in Urban Malawi: A Retrospective Observational Study

Abstract: BackgroundThis study evaluated two models of routine HIV testing of hospitalized children in a high HIV-prevalence resource-constrained African setting. Both models incorporated “task shifting,” or the allocation of tasks to the least-costly, capable health worker.Methods and FindingsTwo models were piloted for three months each within the pediatric department of a referral hospital in Lilongwe, Malawi between January 1 and June 30, 2008. Model 1 utilized lay counselors for HIV testing instead of nurses and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
83
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 39 publications
1
83
3
Order By: Relevance
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
“…We did a stratifi ed analysis of paediatric HIV prevalence in southern and eastern Africa (20 studies) 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27]28,29 versus that in west and central Africa (four). 9,23,28,31 Paediatric HIV prevalence across contexts in southern and eastern Africa was 17·8% (95% CI 12·8-22·7) and prevalence in west and central Africa was 9·8% (95% CI 4·2-15·3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations